Restitution in Criminal Cases Criminal Violence Sexual Abuse in Children in Jayapura City - Maswatu, Aprillia Susanti; Tuharea, Farida; Andrias, Maria Yeti (HORIZON PUBLIC LEGAL STUDIES, 2025)
Study This titled Restitution in Criminal Cases Criminal Violence Child Sexual Abuse in Jayapura City. Violence sexual in children is problem serious affecting​ health physical , mental, and social aspects of the victims. Jayapura City, as capital Papua Province , experienced case violence sexual child increasing.Restitution​ is one of effort For give justice and compensation to the victims. Research This aiming For know How implementation restitution in case Action Criminal Violence Sexual Abuse in Children in Jayapura City, and what obstacles in Handling case act criminal violence sexual abuse in children in Jayapura City. Research This use method Normative Legal Research and Empirical Legal Research . Research law Normative use approach with method learn legislation , theories and related concepts​ with the problem that will be researched . While Empirical Legal Research is Legal Research that analyzes about implementation law in the reality to individuals , groups and institutions law . Data collected via:Interview with Judges and members Renakta who handles case and Observation​ directly in the field . Research results show that restitution given in the form of cash , the amount restitution requested​ from the victim and the victim's family is 65 million , the cases that came in 2024 were 5-6 cases , in court they operate in accordance with rule which are already valid . Submission time restitution in court range between 7 ( seven ) days If No there is a process of effort furthermore and in civil during the application period namely 14 days . The parties Renakta Polda hopes If the victim and the victim's family wants make report about case violence sexual in children must Already Certain with decision said , because the victim and the victim's party did not can to pull out report the with easy , don't Because just promised​ something or lured​ something from party perpetrator.